Managing educational tourism - Ritchie Brent W (New Delhi Viva Books, 2006)
An outline of the main forms of educational tourism, discussing their growth and resulting impacts and management issues from a holistic perspective. Using case studies, the author argues that without adequate research and management the potential impact
Keywords: Educational tourism; Tourism